Fatal case of spotted fever in a patient from Northeastern Brazil - Oliveira, Stefan Vilges de; Costa, Raylene Medeiros Ferreira; Ferreira, Geane; Pereira, Simone Valéria Costa; Amorim, Marinete; Monteiro, Maria Fernanda Melo; Alves, Leucio Câmara; Gazeta, Gilberto Salles (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Spotted fevers are diseases caused by bacterial agents belonging to the spotted-fever (SF) group of the genus Rickettsia. The first documented case of SF in Pernambuco State, Northeast Brazil, was reported here. Also, it is the first case described of fatal SF in Northeast region of Brazil. The patient was a resident of Arcoverde municipality and the probable site of infection lies in Sertania municipality, both in Pernambuco State, a semi-arid region of Brazil. The patient had not visited other areas where SF is endemic. The patient showed clinical manifestations and epidemiological exposure compatible with SF, and the infection was confirmed by molecular biology techniques.